PENGARUH PERSEPSI KEMUDAHAN, PERSEPSI KEGUNAAN, KETERSEDIAAN FITUR DAN LITERASI KEUANGAN TERHADAP PREFERENSI KONSUMEN MENGGUNAKAN BSI MOBILE - Nugroho, Irvan Yusuf; M. Pudjihardjo (Islamic Economics and finance in Focus, 2022)
This research aims to determine the influence of precieved ease of use, precieved usefulness, feature availability and financial literacy on preferences of using the BSI Mobile application by taking a case study at Bank Syariah Indonesia Malang Soetta branch office. In this study, 75 respondents were used as samples, namely customers of Bank Syariah Indonesia at Malang Soetta branch office. The data collection method uses questionnaires distributed online and direct. The data analysis method uses multiple linear regression analysis which is processed using the SPSS 25 application. From the results of the study, it can be found that variables that have a significant effect on preferences for using the BSI Mobile applications are the precieved ease of use, feature availability and financial literacy. While the precieved usefulness variable showed no significant influence on the preferences for using the BSI Mobile applications.